Effect of Environmental Optimism on Responsible Electricity Consumption with Price Concern as a Moderator - Herabadi, Astrid Gisela; Kadarusman, Yohanes B.; Yachinta, Caryn (UI Scholars Hub, 2021)
The study aimed to determine the effect of environmental optimism, as a cognitive–emotional factor, on the responsible use of electricity. Furthermore, it investigated the moderating effect of consumer concern on the price of electricity. An online survey was conducted on 345 young adults in Jakarta selected through the snowball sampling method. Data were analyzed using JASP version 15.0 and IBM SPSS Statistics version 23 reinforced with PROCESS macro. Simple linear regression analysis demonstrated that environmental optimism significantly explains the variance in electricity conservation behavior. The moderating effect of price concern was also substantiated by the result of the data analysis, thus the interaction between environmental optimism and dichotomous predictors of price concern (i.e. high vs low) was found to be statistically significant in moderating the effect of environmental optimism toward electricity conservation behavior. In conclusion, when consumers are initially dominated by price concern (a rational extrinsic motivator), then it reduces the effect of environmental optimism (an emotional intrinsic motivator) on responsible electricity consumption.